Faecal Carriage of Carbapenem-Resistant Enterobacteriaceae among Hospitalized Children in Chidambaram, India: Prevalence and Risk Factors - Ravikant; M Jeya; A John William Felix (International Journal of Pharma and Bio Sciences, 2020)
Carbapenem resistant Enterobacteriaceae (CRE) can cause serious life threatening infection among hospitalized individuals resulting in high morbidity, mortality and costs of hospitalization. Faecal carriage of CRE is a potential risk factor since it can cause endogenous infection and spread rapidly. This study aimed to investigate the prevalence of faecal carriage of CRE and to access risk factors for such carriage among children. A cross-sectional study was conducted, between March and September in 2019. Faecal samples were collected from paediatric wards after 48 hours of admission and cultured. CRE were determined by Kirby Bauer disk diffusion method as per Clinical Laboratory Standards Institute (CLSI 2017) guidelines. Phenotypic determinations of CRE were carried out by Modified Hodge test (MHT), modified Carbapenem Inactivation Method (mCIM) and RAPIDEC Carba NP test. A simpleplex Polymerase chain reaction (PCR) was used to characterise a commonly prevalent gene for carbapenemase. Risk factors associated with faecal carriage were analysed using univariate statistical analysis. Out of 167 faecal samples collected, we found a total of 243 isolates. Eleven isolates from11 inpatient were CRE positive with a prevalence of 6.6 percent by phenotypic methods. Whereas among that only six isolates were CRE positive by molecular analysis. New Delhi metallo B lactamases (NDM1) were found to be the most common carbapenemase producing gene and none of isolates were found with multiple carbapenemase producing genes. We found comparatively high prevalence of faecal carriage of CRE during a non-outbreak situation from paediatric wards. Broader aspects of such finding must be thoroughly searched and discussed.2